2014
DOI: 10.1097/icu.0000000000000080
|View full text |Cite
|
Sign up to set email alerts
|

Trends in corneal transplantation

Abstract: Corneal transplantation has evolved rapidly over the past decade, from full-thickness penetrating keratoplasty towards lamellar keratoplasty to only remove and replace damaged layers of the cornea. Achieving minimal induced astigmatism with excellent visual acuity remains a challenge in corneal transplantation. Further refinements in surgical technique may help improve technical challenges and visual outcomes. In this article, we review changing trends in corneal transplantation and highlight developing medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
66
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 49 publications
1
66
1
6
Order By: Relevance
“…1 This most likely corresponds with the development of Descemet stripping automated endothelial keratoplasty as the predominant treatment for Fuchs dystrophy in the past 10 years. 18,19 About a third of the patients in our study had their wound dehiscence occur within 1 year of PK, indicating that the risk for wound dehiscence is highest in the first postoperative year; others have reported similar conclusions. 20 These results suggest that the use of eye protection during the first postoperative year would reduce the likelihood of wound dehiscence in patients who received a graft.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…1 This most likely corresponds with the development of Descemet stripping automated endothelial keratoplasty as the predominant treatment for Fuchs dystrophy in the past 10 years. 18,19 About a third of the patients in our study had their wound dehiscence occur within 1 year of PK, indicating that the risk for wound dehiscence is highest in the first postoperative year; others have reported similar conclusions. 20 These results suggest that the use of eye protection during the first postoperative year would reduce the likelihood of wound dehiscence in patients who received a graft.…”
Section: Discussionsupporting
confidence: 76%
“…27,28 It will be interesting to learn whether the overall incidence of wound dehiscence will decrease over time for other patient populations, such as those with keratoconus, as newer surgical procedures are being developed to replace PK. 16 26 13 (50.0) 3 (11.5) Tseng et al 17 21 5 (23.8) 6 (28.6) Raber et al 23 10 6 (60.0) 4 (40.0) Lam et al 24 19 11 (57.9) 7 (36.8) Ma et al (current study) 28 6 (21.4) 2 (6.7)…”
Section: Discussionmentioning
confidence: 84%
“…The last revolutionary technique originates once again with Melles et al, who describe the Descemet membrane endothelial keratoplasty (DMEK), the transplantation of an isolated donor DM carrying its endothelium [18]. EK procedures have rapidly gained popularity for transplantation in patients with corneal endothelial diseases [19].…”
mentioning
confidence: 99%
“…The development in surgical treatment of corneal endothelial diseases, with progressive thinning of grafts and its related advantages (13,14) , leads us to conclude that transplantation with cultured en- dothelial cells may represent the next advance in this field (2)(3)(4)(5)(6)(7)(8)(9) . Animal studies have demonstrated promising results (15,16) .…”
Section: Discussionmentioning
confidence: 99%